INTEGRASI KECERDASAN EMOSIONAL DALAM MANAJEMEN PENINGKATAN KINERJA PENDIDIK PROFESIONAL - Yanti Yulianti; Dede Ahmad Kurniadi (Universitas Islam Bunga Bangsa Cirebon, 2023)
The background of this study departs from the gap between increasingly complex professional educator competency demands and performance management practices that have tended to overlook the emotional dimension. Human resource management in educational settings has not fully integrated emotional intelligence capacity as a strategic variable in efforts to improve educator performance quality. This study aims to explore in depth how emotional intelligence can be integrated into the professional educator performance management system, as well as identify patterns, strategies, and barriers that emerge in the integration process. The methodology employed is a qualitative approach with a phenomenological design, involving in-depth interviews, participatory observation, and documentary studies of twelve professional educators across three senior secondary education units in Cirebon City. Data analysis was conducted through thematic analysis techniques using the Miles, Huberman, and Saldana model. The findings reveal that emotional intelligence plays a significant role as a foundation in three aspects of performance management: setting realistic empathy-based goals, providing constructive feedback, and developing continuous professionalism. It was also found that educational unit leaders with high emotional intelligence are able to create a conducive school climate that directly encourages holistic improvement of educator performance. The study affirms that integrating emotional intelligence into performance management is not merely supplementary, but a core element that determines the effectiveness and sustainability of professional educator empowerment.